Faith, Trust, and Service: A Socio-Cultural Analysis of Sharia Insurance Quality in Medan - Muhammad Fauzan; Nur Ahmadi Bi Rahmani; Nursantri Yanti (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
The Islamic insurance industry continues to grow in response to increasing public awareness of finance based on Islamic principles. This study evaluates the service quality of the Sharia insurance provider AJB Bumiputera 1912, Medan Branch, using the Servqual method. Servqual assesses the gap between customer expectations and perceptions across five key dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Employing a descriptive quantitative approach, data were collected through questionnaires distributed to 104 respondents. The analysis involved validity and reliability testing, followed by Servqual calculations. The results reveal that the overall service quality of AJB Bumiputera 1912 Medan Branch meets customer expectations, with an average positive gap of 1.6%. The Tangibles dimension yielded the highest satisfaction level, with a gap of 3%, while the remaining dimensions exhibited relatively minor discrepancies. These findings indicate that the branch provides a high standard of service, yet continuous improvement is essential to further narrow the gap between customer expectations and actual service delivery. Ongoing service quality evaluations are recommended to enhance the company’s competitive edge within the Sharia insurance sector